2005
DOI: 10.1021/bm050361c
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characterization of in Situ Cross-Linkable Hyaluronan Hydrogels

Abstract: This report investigates the rheological properties of cross-linked, thiol-functionalized HA (HA-DTPH) hydrogels prepared by varying the concentration and molecular weight (MW) of the cross-linker, poly(ethylene glycol) diacrylate (PEGDA). Hydrogels were subsequently cured for either short-term (hours) or long-term (days) and subjected to oscillatory shear rheometry (OSR). OSR allows the evaluation and comparison of the shear storage moduli (G'), an index of the total number of effective cross-links formed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
161
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 33 publications
13
161
0
Order By: Relevance
“…Stiffness measurements were performed by using an AR-G2 rheometer (TA Instruments) with a standard aluminum parallel plate geometry of 20 mm. Hydrogels were subjected to a stress sweep (46), and their storage moduli (GЈ) were compared under the same physical conditions. To analyze the effects of varying ECM elasticity on cell shape, we cultured CE cells for 6 h on hydrogels of varying stiffness at a low density (1,000 cells per squared centimeter) to minimize cell-cell interactions.…”
Section: Methodsmentioning
confidence: 99%
“…Stiffness measurements were performed by using an AR-G2 rheometer (TA Instruments) with a standard aluminum parallel plate geometry of 20 mm. Hydrogels were subjected to a stress sweep (46), and their storage moduli (GЈ) were compared under the same physical conditions. To analyze the effects of varying ECM elasticity on cell shape, we cultured CE cells for 6 h on hydrogels of varying stiffness at a low density (1,000 cells per squared centimeter) to minimize cell-cell interactions.…”
Section: Methodsmentioning
confidence: 99%
“…[164] Covalent in situ gelation chemistries, meanwhile, offer the dual benefits of fast reactions as well as more predictable and tunable degradation kinetics (or, in some cases, nondegradability) and as such have even broader potential utility. A variety of chemistries including amine-aldehyde (Schiff bases/imines), [165,166] thiol-thiol (disulfide), [167] hydrazide-aldehyde (hydrazones), [168,169] hydroxylamine-aldehyde (oximes), [170] thiol-maleimide (thiosuccinimides), [171] (thiol or amine)-alkene (Michael adducts), [172] and alkyne-azide (triazoles) [173] have been reported that meets the criteria of fast reactions that occur spontaneously upon mixing in water, with the chemistries listed above in the approximate order of the stability of the resulting crosslink in water.…”
Section: Solvent/additive-free Hydrogelsmentioning
confidence: 99%
“…In the absence of AuNPs, soft disulfi de-crosslinked gels with a G â€Č , or storage modulus, of 10-20 Pa form. [ 11 ] First, to confi rm biocompatibility, a LIVE/DEAD viability/ cytotoxicity assay and an MTS mitochondrial activity assay was performed on cells cultured on the surface of AuNP-sECM hydrogels. NIH 3T3, HepG2 C3A, and Int-407 cells showed > 95% viability at day 3 and at day 7 (Supporting Information, Figure S1).…”
Section: Doi: 101002/adma201001436mentioning
confidence: 99%